Implementation of Anti-Windup PI Speed Controller for Induction Motor Drive Using dSPACE and Matlab/Simulink Environment - Talib, Md Hairul Nizam; Ibrahim, Zulkifilie; Abd. Rahim, Nasrudin; Abu Hasim, Ahmad Shukri (AENSI Publishing Corporation, 2013)
This paper presents the design, analysis and implementation of speed control drive indirect Field Oriented Control (FOC) induction motor using a dSPACE DS1103 digital-signal-processor-based real-time data acquisition control system and MATLAB/Simulink environment. The details design of speed control indirect Field Oriented Control (FOC) induction motor drive with Anti-Windup PI controllers' (AWPI) is discussed. In addition, the controller designed is focused on the mathematical determination of proportional integral (PI) controller which is usually obtained by trial and error approached. Three PI controllers are used in speed and current loops to control the Space Vector Pulse Width Modulation Technique (SVPWM) in FOC scheme. Simulation and experimental test results at rated voltage, speed and load disturbance are verified the effectiveness of the design approached.